(untitled) - BALARA, Milan (Trends in education, 2009)
The speed control system of an externally-excited DC motor without tachogenerator (TG) is actually a discrete control circuit where the motor current is intentionally cut-off so that the induced armature voltage may be sensed. This voltage (proportional to the angular speed of a motor) is stored in analog memory during one sample period and processed by the speed controller. That's how the speed control of a motor without TG is carried out - angular speed is sensed by the motor itself.
Keywords: Tachogenerator; analog memory; controller; control system; discrete control circuit.